(untitled) (Research, Society and Development, 2020)
Objective: To analyze the structure of social representations of health professionals about communicable diseases. Method: qualitative study supported by the Theory of Social Representations, in its structural approach, composed of an intentional and non-probabilistic sample of 90 health professionals. Data collected by the questionnaire of free evocations to the term inducer transmissible diseases and analyzed by the technique of the quadrant of four houses, aided by the software Ensemble of Programs Permettant l’analyse des Evocations 2005 and by the similitude analysis. Results: The results showed a representational structure of health professionals on communicable diseases consisting of three dimensions: individual; social and imagery, which were managed by a central core formed by the terms STD, HIV and ignorance. The dimensions and central core of this representational structure indicated the meanings as the absence of individual and collective practices in the prevention and treatment of these morbid entities. Conclusion: The representational structure made it possible to identify the need for changes in professional practices to face these diseases in order to guide new individual and collective attitudes in the prevention, promotion and rehabilitation of communicable diseases.